2010
DOI: 10.1088/0022-3727/43/28/285501
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally grown nanostructured WO3 films and their electrochromic characteristics

Abstract: We report the synthesis of nanostructured tungsten trioxide (WO 3) films and their electrochromic characteristics. Plate-like monoclinic WO 3 nanostructures were grown directly on fluorine-doped tin oxide glass substrates by a simple and low-cost crystal-seed-assisted hydrothermal method. The growth mechanism of the film is investigated. HRTEM analysis reveals the single crystalline quality of the WO 3 nanostructure. The film exhibits tunable transmittance modulation under different voltages and repetitive cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 34 publications
2
83
2
Order By: Relevance
“…7 shows the dynamic coloration/bleaching characteristics of the ECD, recorded at the wavelength of 700 nm. The coloration and bleaching times (c and b), defined as time required for achieving 70 % of the total transmission change [37,38] was found to be 9.3 s and 1.2 s respectively, which means that the coloring kinetics is slower than the bleaching one. The faster bleaching time is due to the good conductivity of the tungsten bronze (KxWO3) and the conductor (KxWO3) to semiconductor (WO3) transition.…”
Section: Figure 6 Optical Density Variationwith Respect To the Chargmentioning
confidence: 99%
“…7 shows the dynamic coloration/bleaching characteristics of the ECD, recorded at the wavelength of 700 nm. The coloration and bleaching times (c and b), defined as time required for achieving 70 % of the total transmission change [37,38] was found to be 9.3 s and 1.2 s respectively, which means that the coloring kinetics is slower than the bleaching one. The faster bleaching time is due to the good conductivity of the tungsten bronze (KxWO3) and the conductor (KxWO3) to semiconductor (WO3) transition.…”
Section: Figure 6 Optical Density Variationwith Respect To the Chargmentioning
confidence: 99%
“…The detailed procedures for preparing crystal seed layers can be found elsewhere [24]. In a typical experiment for preparing the precursor, Na 2 WO 4 ·2H 2 O (0.0655 g) was dissolved into 20 mL of de-ionized water and then 4 mL of HCl was added into the solution until no more precipitate was formed.…”
Section: Preparation Of Crystal Seed Layers Precursor and Hydrothermmentioning
confidence: 99%
“…For electrochromic applications, WO 3 nanostructures need to be assembled as a thin film on conductive substrates and the microstructures of the film concerning the electrochromic performance largely depend on the film assembling techniques and processing conditions. Such thin films of WO 3 have been grown by vacuum deposition [21], electrodeposition [22], sol-gel [23] and hydrothermal method [24,25]. Hydrothermal approach is one of the most promising methods for fabricating WO 3 film because of its merits of low cost, low reaction temperature, flexible substrate selection and easy scalingup for production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason for the photocurrent enhancement is believed to be attributed to the increased surface area of the etched sample due to the porous structure. The decrease of the overpotential is probably attributed to the numerous pores, too, which is considered to be beneficial for the hole transfer [11,12]. Further investigations revealed that when the potential was lower than ~1.4 V vs. RHE the etching would not run obviously.…”
Section: Resultsmentioning
confidence: 98%